EP300/#876 Impact of initiation timing of niraparib maintenance treatment in newly diagnosed advanced ovarian cancer. (4th December 2022) - Wang, Jing; Wu, Lingying; Zhu, Jianqing; Yin, Rutie; Pan, Lingya; Kong, Beihua; Zheng, Hong; Liu, Jihong; Wu, Xiaohua; Wang, Li; Huang, Yi; Wang, Ke; et al.
Abstract : Objectives: PARPi maintenance treatment (MT) is indicated for patients with newly diagnosed advanced ovarian cancer (aOC) after first-line platinum-based chemotherapy (1LCT). However, the impact of initiation timing of PARPi MT is unclear. This study aims to compare the efficacy and safety of niraparib MT initiated after different intervals upon completion of 1LCT. Methods: This is a post hoc analysis of the PRIME phase 3 study (NCT03709316 ). Adults with newly diagnosed aOC and a response to 1LCT were randomized 2:1 to receive niraparib or placebo within 12 weeks upon completing of 1LCT. The primary endpoint was PFS by BICR. Subgroups comprised patients who initiated MT <9 weeks or ≥9 weeks upon completion of 1LCT. Results: Key baseline characteristics were overall balanced between groups ( table 1 ). Median PFS (95% CI) was 29.4 months (16.9-not estimable) with niraparib versus 8.3 months (5.5–11.0) with placebo (HR =0.31; 95% CI, 0.20–0.48) for the <9 weeks group and was 24.7 months (16.5-not estimable) with niraparib versus 10.8 months (6.5–24.9) with placebo (HR=0.60; 95% CI, 0.41–0.89) for the ≥9 weeks group ( figure 1 ). Grade ≥3 hematological adverse events occurred in similar proportions of niraparib-treated patients for the <9 weeks and ≥9 weeks groups: anemia (19.3% versus 17.0%), platelet count decreased (18.4% versus 10.6%), and neutrophil count decreased (15.8% versus 18.4%). Conclusions: Whether initiated <9 weeks or ≥9–12 weeks upon completion of 1LCT, niraparib MT conferred clinically significant benefit versus placebo to patients with newly diagnosed aOC, without significant impact on safety profile.